The Use of Explainer Video and Instagram in Improving Students’ Writing Skills - Dewang Dewani Nila Kandi; Afrianto Afrianto; Supriusman Supriusman (FKIP - Universitas Riau, 2026)
This research is a mixed method research including both qualitative and quantitative data. The purpose of this study is to determine whether there is a significant effect of explainer video and Instagram in improving students' skills to write recount texts, whether the use of explainer videos increases students' interest in learning recount texts and exploring whether students’ experiences in learning recount text by using Instagram are improved. This study uses primary data obtained from assessing the results of students’ writing tests, questionnaires of students’ interests and interview of students’ experiences. Data analysis uses a paired sample t-test and validity test for writing test and questionnaire with one-on-one interview. The results of this study found that there were differences in the skills to write recount texts between the experimental class and the control class after being given treatment through Instagram social media and explainer videos with questionnaire show that students' perceptions regarding the use of explainer videos in class generally have a perception of